Effect of cadmium on seed germination, growth and pigments content of Zinnia plant - M. Vijayaragavan2, D. Thamayanthi1*, P.S. Sharavanan1 and (Current Botany, 2011)
The present work made to the effect of cadmium on seed germination, growth and pigments content of Zinnia elegans (L.) plant. The experiment was conducted at Botanical Garden, Department of Botany, Annamalai University, Tamil Nadu, during the period of January to March 2011. In the pot culture experiment, Zinnia plants were analysed on three different sampling (viz., 15th, 30th and 45th) days, in soil amended with various levels of cadmium (10, 20, 30, 40, and 50 mg kg-1 soil). The inner surfaces of pots were lined with a polythene sheet. Each pot containing 3kg of air dried soil. Six seeds were sown in each pot. All pots were watered to field capacity daily. Plants were thinned to a maximum of three per pots, after a week of germination. Cadmium at all levels (10,20,30,40 and 50mg kg-1) tested, decreased the seed germination, growth parameters such as, root and shoot length, number of leaves, total leaf area and biochemical constituents such as, chlorophyll-a, chlorophyll-b, total chlorophyll and carotenoid contents of zinnia plants compared to untreated plants.